The Spectrum of Religiousness, or What Makes an Object Religious. Habits, Patterned Evidence and Religious Meanings of Image-Objects in Pompeii - Rieger, Anna-Katharina (ARYS. Antigüedad: Religiones y Sociedades, 2020)
How do image-objects obtain a religious meaning? When can we interpret material evidence as traces of a religious ritual? These questions are central to the archaeology of religion, but often answered in favor of religion without sound criteria. Using examples from Pompeii I look into “material religion” through the lens of viewing habits and habitualized practices embedded in and shaping social and cultural habitus in a Roman city of the 1st cent. CE. This practice-oriented approach to religion and material culture allows for a more nuanced interpretation of when and how people in Graeco-Roman antiquity conceived of an image-object as religious and ascribed a religious meaning to it. Based on an understanding of religion as communication with supra-human agents, the notion of a “spectrum of religiousness” softens the black-and-white view on motifs and objects as either religious or profane. The distinction of a gradually varying perception of image-objects is archaeologically based on both loosely assembled evidence (e.g. the iconographical and material remains in a house) or intentionally arranged evidence (e.g. niches with altars in front of them). In the repetition of such material reflections of practices the religious character of imageobjects comes to the fore.